2001
DOI: 10.1067/mva.2001.112209
|View full text |Cite
|
Sign up to set email alerts
|

New experiences with absolute ethanol sclerotherapy in the management of a complex form of congenital venous malformation

Abstract: Absolute ethanol sclerotherapy alone can deliver excellent results in complex forms of venous malformations with considerable but acceptable morbidity and may be able to reduce the morbidity involved with the conventional surgical therapy alone on complex forms of venous malformation. No recurrence or deterioration of the therapy results was observed during the follow-up period (average, 10.2 months) after the completion of multistaged therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
127
1
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(137 citation statements)
references
References 7 publications
3
127
1
5
Order By: Relevance
“…29) Therefore, the strategy for the VM management should be different from those for the AVM, and not all the VM lesions should require treatments immediately and the traditional conservative approach is still recommended for the vast majority of VM lesions. 30,31) A typical VM lesion without abnormal bone growth involvement can be monitored until the age of two or more years when the child is matured enough to tolerate various diagnosis and treatment procedures.…”
Section: Diacnosis In Generalmentioning
confidence: 99%
“…29) Therefore, the strategy for the VM management should be different from those for the AVM, and not all the VM lesions should require treatments immediately and the traditional conservative approach is still recommended for the vast majority of VM lesions. 30,31) A typical VM lesion without abnormal bone growth involvement can be monitored until the age of two or more years when the child is matured enough to tolerate various diagnosis and treatment procedures.…”
Section: Diacnosis In Generalmentioning
confidence: 99%
“…Therefore, in many cases, the aim of treatment for vascular malformation is for symptomatic relief rather than a cure. [5][6][7] Before invasive treatment for vascular malformations, detailed imaging diagnostic procedures such as catheter angiography are required. Because the symptoms of this patient were controlled conservatively, she did not need to undergo further invasive examination or intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Although effective, data showed that ethanol sclerotherapy was associated with limitations and major complications (local and systemic), including severe pain requiring general anesthesia, ethanol toxicity, and localized tissue necrosis [75][76][77] . In a study of 87 patients with venous malformations treated with 98 sessions of ethanol sclerotherapy Lee et al reported outstanding results with 95% initial success with no recurrence in 71 patients at a mean follow-up of 24 months 78 .…”
Section: Treatmentmentioning
confidence: 99%